(Language Modernity and modern in the reflections of the wings of silence of the poet (Hamid Abdul Samad al-Basri - Abdul Samad, Worod Hamed (Journal of Humanities & Social Sciences, 2017)
There is no doubt that his words industry and distinctiveness in the selection of meanings for the formulation of meaning may have contributed to the elaboration of poetic language ideas through text vocabulary, and to allocate the aesthetic with its own standards led to perceptions of a more profound, and more comprehensive eloquence .This is exemplified by the reflections of Hamid Al- Basrawi between Single divulge, and other harbor and everything in between lies your taste, as it formed the language of the manifestations of memory, qualifying on the past and charged the reality that clinch meaning through those narrow lanes, barbed, the continuity of a sense of the past is only a translation of the poet’s life conscious of reality through them, because the reality is often a deadlock to focus upon hassles and continuous effort, the escape to a fantasy world and the anniversary is a movement and vitality that will restore the poet and the receiver to a hidden phenomenon worlds, between the points (ego), (they are) and (we), artistic the vision specifically lies in the spontaneous behavior that brought him poet and vocabulary that guided the meaning of the privacy of its model and method put forward and how awareness of the breakdown of titles ranging from the first poem in the book until the conclusion as such an integrated living units in the context of essentially poetic duplicates the former by later.